Are Energy Block Chain Currencies Affected by the Major US Energy Markets? - Gurrib, Ikhlaas (International Journal of Energy Economics and Policy, 2018)
While various economies have started to embark on a gradual shift towards renewable sources of energy, energy block chain based crypto currencies have emerged. The purpose of this study is to shed fresh light into whether an energy commodity price index (ENFX) and energy block chain based crypto price index (ENCX) can be used to predict movements in the energy commodity and energy crypto market. Using principal component analysis over daily data of crude oil, heating oil, natural gas, and energy based cryptos, the ENFX and ENCX indices are constructed, where ENFX (ENCX) represents 94% (88%) of variability in energy commodity (energy crypto) prices. Natural gas price movements were better explained by ENCX, and shared positive (negative) correlations with cryptos (crude oil and heating oil). Using a vector autoregressive model (VAR), while the 1-day lagged ENCX (ENFX) was significant in estimating current ENCX (ENFX) values, only the lagged ENCX was significant in estimating current ENFX values. Granger causality tests confirmed the two markets do not granger cause each other. One standard deviation shock in ENFX had a negative effect on ENCX, and one standard deviation shock in ENCX left ENFX unaffected. Both indices had 1 structural break on different dates. Overall findings suggest that while the ENFX and ENCX are good representative of commodity energy prices and energy block chain based cryptos respectively, the two markets are not robust determinants of each other. Keywords: energy crypto currencies, energy commodity, VAR, impulse response, structural break JEL Classifications: Q02, Q41, Q42, Q47 DOI: https://doi.org/10.32479/ijeep.7163